2020
DOI: 10.1155/2020/8813558
|View full text |Cite
|
Sign up to set email alerts
|

The Function and Role of the Th17/Treg Cell Balance in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic, inflammatory, and autoimmune disorder. The pathogenesis of IBD is not yet clear. Studies have shown that the imbalance between T helper 17 (Th17) and regulatory T (Treg) cells, which differentiate from CD4+ T cells, contributes to IBD. Th17 cells promote tissue inflammation, and Treg cells suppress autoimmunity in IBD. Therefore, Th17/Treg cell balance is crucial. Some regulatory factors affecting the production and maintenance of these cells are also important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 78 publications
(59 reference statements)
4
148
0
1
Order By: Relevance
“…Treg cells and Th17 cells perform specialized functions through distinct transduction pathways and restrict each other in terms of differentiation and function (4). Tregs have immunosuppressive properties that can also be present in the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Treg cells and Th17 cells perform specialized functions through distinct transduction pathways and restrict each other in terms of differentiation and function (4). Tregs have immunosuppressive properties that can also be present in the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, is characterized by chronic relapsing intestinal inflammation. Although the etiology of IBD is ill-defined, the dysregulation of proinflammatory Th17 cells and anti-inflammatory Treg cells contributes to the pathogenesis of IBD ( 78 , 79 ). Using CD4-Cre +/ Tg Mettl14 FL / FL conditional knockout mice, Thomas X et al firstly demonstrated that METTL14 deficiency in T cells causes the development of spontaneous colitis by dramatically increasing the release of Th17 cell-related proinflammatory cytokines ( 80 ).…”
Section: A Modification In Autoimmune Diseasesmentioning
confidence: 99%
“…Along with its role in innate immunity, it also plays a role in adaptive immunity by contributing to the differentiation of CD4+ T cells into various subsets of helper T cells (Th1, Th2, Th17) and Treg cells [ 170 ]. Th17 and Treg cells maintain a balance to ensure homeostasis, and dysregulation increases IBD susceptibility [ 171 ]. Singh et al found that 8–12-week-old miR-155 KO mice have lower levels of Th17 cells in the mesenteric lymph nodes in response to chronic DSS-induced colitis (1% DSS administered for seven days followed by seven days of water, treatment regime repeated for three cycles) along with reduced pro-inflammatory cytokines [ 116 ].…”
Section: Microrna As a Therapeutic Target In Ibdmentioning
confidence: 99%